2013
DOI: 10.1016/j.ijgo.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after loop electrosurgical excision procedure for cervical intraepithelial neoplasia

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Objective: To determine pregnancy outcomes among women who underwent loop electrosurgical excision procedure (LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The finding of a poorer PPV for a short cervix in women with a past history of cervical surgery is particularly important in light of previous studies that have found an increased rate of midtrimester short cervix in this population . Although it has been reported that the volume of cervical tissue excised for the biopsy may elevate the risk of SPTB, other studies conclude that the increased risk is independent of the presence of the mean shorter cervical length found in this group of women …”
Section: Discussionmentioning
confidence: 85%
“…The finding of a poorer PPV for a short cervix in women with a past history of cervical surgery is particularly important in light of previous studies that have found an increased rate of midtrimester short cervix in this population . Although it has been reported that the volume of cervical tissue excised for the biopsy may elevate the risk of SPTB, other studies conclude that the increased risk is independent of the presence of the mean shorter cervical length found in this group of women …”
Section: Discussionmentioning
confidence: 85%
“…Other studies in this group of women used only a single measure of CL, and many reported CL < 30 mm, rather than < 25 mm, as being significant for SPTB prediction. If the cause of SPTB in women with previous excisional cervical surgery was indeed due to loss of cervical volume, then the CL predicting SPTB ought to be shorter than in women with different risk factors for SPTB.…”
Section: Epidemiology and Definitionsmentioning
confidence: 99%
“…4,5). While effective, such interventions have a number of undesirable possible side effects including pain and cervical incompetence leading to preterm birth and low infant birthweight (6,7). Moreover, even successful procedures of this nature may not clear infection by high-risk HPV (HR-HPV), thus leaving the patient at risk for recurrence of disease (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%